Interactive governance : advancing the paradigm - Torfing, Jacob (New York : Oxford University Press, 2012)
"Governance has become one of the most commonly used concepts in contemporary political science. It is, however, often used to mean a variety of different things. This book helps to clarify this conceptual muddle by concentrating on one variety of governance-interactive governance. The authors argue that although the state may remain important for many aspects of governing, interactions between state and society represent an important, and perhaps increasingly important, dimension of governance. These interactions may be with social actors such as networks, with market actors or with other governments, but all these forms represent means of governing involving mixtures of state action with the actions of other entities.This book explores thoroughly this meaning of governance, and links it to broader questions of governance. In the process of explicating this dimension of governance the authors also explore some of the more fundamental questions about governance theory. For example, although governance is talked about a great deal political science has done relatively little about how to measure this concept. Likewise, the term multi-level governance has become widely used but its important to understand that idea more fully and see how it functions in the context of interactive forms of governance. The authors also link governance to some very fundamental questions in political science and the social sciences more broadly. How is power exercised in interactive governance? How democratic is interactive governance, and is democratic governance always advanced through transparency?"--Publisher's website.
Introduction -- The governance debate and the rise of interactive governance -- Governance in other disciplines: one approach or many? -- Power and politics in interactive governance -- Measuring governance -- Horizontal, vertical, and diagonal governance -- Institutionalizing interactive governance -- Metagovernance: the art of governing interactive governance -- New roles and role dilemmas in interactive governance -- Assessing and improving effective interactive governance -- Assessing and improving the democratic quality of interactive governance -- Transparency and governance -- Conclusions.
Includes bibliographical references (p. 240-264) and index.
Keywords: Public administration; Government accountability; Political science; Power (Social sciences)